Finding Home: Paule Marshall’s “The Chosen Place, the Timeless People” - Stulov, Yuri (Respectus Philologicus, 2018)
[full article and abstract in English]The paper deals with the novel “The Chosen Place, the Timeless People” by Paule Marshall, one of the most significant precursors of the modern generation of African American women writers who were instrumental in voicing the concerns and aspirations of millions of black women. It develops some of the themes the writer addressed in her first novel “Brown Girl, Brownstones” and raises topical issues of power and domination, connections between the historical past and present, postcolonial mentality, individual and collective identity, racism, gender inequality, complex relationship between the oppressed and the oppressors, men and women in a male-dominated society, and women’s struggle for self-identification and self-determination. The novel was published in 1969, a critical year in the Civil Rights movement that paved the way for major changes in the social and political life of the United States, and signified the emergence of black feminist writing focusing on the female protagonist of mixed descent who challenges the accepted views and mores and helps to introduce the new awareness of what should be done to break with the miserable past.
Keywords: African American Fiction, Feminism, Gender, Postcolonialism